2006
DOI: 10.1590/s0080-62342006000400013
|View full text |Cite
|
Sign up to set email alerts
|

Análise dos óbitos em idosos no Estudo SABE

Abstract: The Pan-American Health Organization coordinated a survey called SABE - acronym for Health, Wellbeing and Aging carried out in seven Latin America and Caribbean countries. In Brazil, it was developed in the city of São Paulo in 2000. On a sample of 2,143 elderly people was applied an instrument, made up of eleven sections, in two parts. The present study was aimed at characterizing and analyzing the death causes of the elderly people during the period of the SABE data collection. From the total deaths, 55.3% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
18

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 5 publications
1
10
0
18
Order By: Relevance
“…As demographic changes occur with increased expectancy of life, the increase of the elderly population is also observed, including within ICUs (2) . Studies indicate that whatever the health indicator analyzed, results show a greater proportion of disorders among those older than 60 years of age accruing from chronic diseases that should be identified early, treated and monitored to reduce mortality and costs from healthcare (3)(4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demographic changes occur with increased expectancy of life, the increase of the elderly population is also observed, including within ICUs (2) . Studies indicate that whatever the health indicator analyzed, results show a greater proportion of disorders among those older than 60 years of age accruing from chronic diseases that should be identified early, treated and monitored to reduce mortality and costs from healthcare (3)(4) .…”
Section: Introductionmentioning
confidence: 99%
“…In situations when the body is overloaded, the homeostatic balance is harmed, which makes an elderly individual more susceptible to disorders and diseases (3,5) . Additionally, elderly patients' responses to treatment, when compared to younger patients, may be harmed given a low physiological reserve, inherent to the aging process.…”
Section: Introductionmentioning
confidence: 99%
“…15 been done, and the main causes of death in this population were cardiovascular diseases, neoplasms, respiratory diseases, gastrointestinal diseases, endocrine, nutritional or metabolic diseases and others. (5,(7)(8)(9) The analysis of risk factors for death in elderly patients showed that advanced age was the strongest prognostic factor. Male gender is also considered a risk factor for death in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Male gender is also considered a risk factor for death in the elderly. (8,9) There is a lack of studies investigating risk factors for death among critically ill elderly patients. The present study was conducted to investigate the factors associated with death in a population of critically ill elderly patients admitted to an ICU in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Este verificou que as taxas de mortalidade por doenças cardiovasculares aumentavam conforme o avançar da idade; e ainda, que são estas as doenças que representam quase metade do total dos óbitos (47%) na população idosa. 22 Segundo Marin et al, 21 muitas dessas enfermidades, por serem crônicas, demandam alto custo na assistência à saúde, além de propiciarem o surgimento de complicações com grande interferência no grau de dependência e qualidade de vida das pessoas. Entre as pessoas idosas, é comum a ocorrência de mais de uma condição crônica simultânea, elevando o risco de complicações, de ocorrência de incapacidades e instalação de quadros de dependência, que, em última análise, comprometem a qualidade de vida tanto dos idosos quanto de seus familiares, além de representarem um desafio para as políticas públicas de saúde.…”
Section: Introductionunclassified